Metal piece and machining process thereof

By setting a groove structure on the inside of the titanium alloy frame and adding flow aids to the aluminum alloy liquid, the problem of stress differences caused by the difference in thermal expansion coefficients between titanium alloy and aluminum alloy is solved, and the adhesion and structural stability of the two are significantly improved. .

CN119457727AActive Publication Date: 2025-02-18GUANGZHOU ZHONGSHAN FASTENER CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411625036.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The stress differences caused by the difference in thermal expansion coefficient between titanium alloy and aluminum alloy affect their adhesion, which may lead to the instability of the mobile phone structure and the decline in waterproof and dustproof performance.

Method used

The groove structure is arranged on the inside of the titanium alloy frame, so that the aluminum alloy liquid can be infused and forms a mechanical locking structure with the titanium alloy frame after cooling, improving adhesion, and adding flow aids to the aluminum alloy liquid to improve flow performance .

Benefits of technology

It significantly improves the adhesion between titanium alloy and aluminum alloy, effectively balances the stress caused by the difference in thermal expansion coefficient, and enhances the stability of the structure and waterproof and dustproof performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457727A_ABST
    Figure CN119457727A_ABST
Patent Text Reader

Abstract

The invention provides a metal piece and a machining process thereof, and relates to the technical field of titanium alloy frame machining, and the metal piece comprises a titanium alloy frame and an aluminum alloy internal component; a plurality of grooves are formed in the inner side of the titanium alloy frame and are used for pouring aluminum alloy liquid; wherein the aluminum alloy liquid contains a flow promoter. The groove structures are formed in the inner side of the titanium alloy frame, aluminum alloy liquid can be poured into the grooves, the grooves and the titanium alloy frame form a tight mechanical lock catch structure after cooling, and the structure can remarkably improve the adhesive force between the two materials; and stress generated due to difference of thermal expansion coefficients can be better balanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy frame processing, in particular to a metal part and a processing technology thereof. Background Art

[0002] With the rapid development of global science and technology, titanium alloy frame structure mobile phones are like a fresh trend, leading the current smartphone market. This innovative design not only highlights the perfect fusion of technology and aesthetics, but also reflects a deep insight into material science and manufacturing processes. At the same time, a material that shares the characteristics of light weight and high strength with titanium alloys, titanium metal, has gradually emerged and is regarded as a revolutionary choice in the field of mobile phone materials. Although titanium metal and titanium alloys show similarities in basic composition and certain physical properties, titanium alloys can often show more outstanding hardness performance, better corrosion resistance and better comprehensive mechanical properties through precise alloying treatment. It is these performance advantages beyond the ordinary that pave a broader road for the widespread application of titanium alloys in future smartphones. It can not only be used as the preferred material for the frame structure of mobile phones, providing both strong and light support, but also can be cleverly applied to other key components of mobile phones, such as precision buttons, elegant frames, etc., thereby improving the overall durability of the mobile phone while giving the product a more unique aesthetic charm.

[0003] On the other hand, aluminum alloy, as a traditional material for the internal components of mobile phones, is also important. Aluminum alloy has long been an ideal material for the internal support structure, precision cooling system and other key components of mobile phones due to its many advantages such as low density, high strength, excellent processing performance and high cost-effectiveness. The widespread use of aluminum alloy not only effectively reduces the overall weight of mobile phones, allowing users to enjoy a lighter and more portable experience, but also ensures that the mobile phone still has sufficient structural strength and stability while maintaining a thin and light design, providing a solid guarantee for the durability and reliability of the mobile phone.

[0004] However, it is worth noting that there are significant differences in the key physical property of thermal expansion coefficient between titanium alloy and aluminum alloy. The thermal expansion coefficient is an important physical indicator to measure the degree of dimensional change of a material when the temperature changes. The difference in this property is undoubtedly a challenge that cannot be ignored for the design and manufacture of mobile phones. When the mobile phone is in different temperature environments, due to the different thermal expansion coefficients of the titanium alloy frame and the aluminum alloy internal components, they will expand or contract to different degrees. This difference in dimensional change may affect the bonding force between the two, and even in some extreme cases, tiny gaps or looseness may occur. These problems will not only pose a potential threat to the overall structural stability of the mobile phone, but may also have an adverse effect on the waterproof and dustproof performance of the mobile phone, because those seemingly insignificant gaps are likely to become a "back door" for moisture and dust to invade, thereby affecting the normal function and service life of the mobile phone. Therefore, how to effectively deal with the challenges brought by the difference in thermal expansion coefficients between titanium alloy and aluminum alloy in the design and manufacturing process has become an important problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above-mentioned problems, the present invention aims to provide a metal part and its processing technology. The present invention arranges a groove structure on the inner side of the titanium alloy frame. These grooves can allow aluminum alloy liquid to be poured into them, and form a tight mechanical locking structure with the titanium alloy frame after cooling. This structure can significantly improve the adhesion between the two materials and can also better balance the stress caused by the difference in thermal expansion coefficients.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a metal part, which includes a titanium alloy frame and an aluminum alloy internal component;

[0008] A plurality of grooves are provided on the inner side of the titanium alloy frame, and the grooves are used for pouring aluminum alloy liquid;

[0009] Wherein, the aluminum alloy liquid contains a flow aid.

[0010] Further, based on the above technical solution, the groove includes at least one of a dovetail groove or a T-slot;

[0011] And / or, the edge of the groove is a smooth curve.

[0012] Further, based on the above technical solution, the size of the notch connecting the groove and the inner side of the titanium alloy frame is 100-500 μm;

[0013] The size ratio of the groove bottom to the groove mouth is (2.5-3.5):1.

[0014] Further, on the basis of the above technical solution, the flow aid includes one or more of silane, silicone, vapor deposited silicon, aluminum chloride, sodium silicate or magnesium oxide;

[0015] The amount of the flow aid added is 0.001-0.01% of the total mass of the aluminum alloy liquid;

[0016] The temperature of the aluminum alloy liquid is 740-780°C.

[0017] Furthermore, based on the above technical solution, the groove is formed by 3D printing.

[0018] Furthermore, based on the above technical solution, a plurality of bosses are provided on the inner side of the titanium alloy frame;

[0019] The boss includes at least one of a dovetail boss and a T-shaped boss.

[0020] Further, on the basis of the above technical solution, the titanium alloy includes one of Ti-6Al-4V titanium alloy, Ti-8Al-1Mo-1V titanium alloy, TC4 titanium alloy or TA18 titanium alloy;

[0021] And / or, the aluminum alloy includes one of 6013 aluminum alloy, 7R03 aluminum alloy, 6061 aluminum alloy, 6063 aluminum alloy, 7005 aluminum alloy, 7075 aluminum alloy or 2117 aluminum alloy.

[0022] The present invention also provides a processing technology for the above-mentioned metal part, comprising the following steps:

[0023] S1: 3D printing is used to prepare the titanium alloy frame and the grooves and bosses inside the titanium alloy frame;

[0024] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid, and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0025] S3: Polishing, anodizing and aging heat treatment are performed on the rough metal parts to obtain finished metal parts.

[0026] Further, on the basis of the above technical solution, in step S3, the anodizing is to place the polished metal part in an electrolytic cell, the electrolyte in the electrolytic cell includes a 0.5-2 mol / L sulfuric acid solution, 0.5-1.0 mol / L oleic acid hydroxyethyl imidazoline and 0.5-1.0 mol / L sodium sulfate mixture, a titanium alloy frame is used as an anode, graphite is used as a cathode, direct current electrolysis is performed for 20-40 s, and the current density is controlled at 0.10-0.30 A / cm 2 , the bath temperature is controlled at 30-50°C, and after completion, it is rinsed with deionized water and dried;

[0027] And / or, in step S3, the polishing treatment includes chemical treatment and / or mechanical treatment.

[0028] Further, on the basis of the above technical solution, in step S3, the aging heat treatment includes: hot pressing and curing the anodized metal part at a curing temperature of 800-950° C. for 30-60 minutes, and cooling;

[0029] Then heat to 500-600℃, keep for 6-10h, and obtain the finished metal part after cooling.

[0030] The present invention provides a metal part and a processing technology thereof, and the beneficial effects are as follows:

[0031] 1. The present invention provides a groove structure on the inner side of the titanium alloy frame. These grooves allow aluminum alloy liquid to be poured into them and form a tight mechanical locking structure with the titanium alloy frame after cooling. This structure can significantly improve the adhesion between the two materials.

[0032] 2. In the present invention, adding a flow aid to the aluminum alloy liquid can significantly reduce the surface tension of the aluminum alloy liquid, thereby greatly improving its flow performance, so that the aluminum alloy liquid can flow more smoothly into the designed smaller groove during the pouring process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic diagram of the groove structure inside the titanium alloy frame provided by the present invention;

[0035] icon:

[0036] 1. Titanium alloy frame; 2. Dovetail groove; 21. Dovetail groove opening; 22. Dovetail groove bottom; 3. T-slot; 31. T-slot opening; 32. T-slot bottom; 4. Dovetail boss; 5. T-boss. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] According to a first aspect of the present invention, there is provided a metal part, the metal part comprising a titanium alloy frame 1 and an aluminum alloy internal component;

[0040] The inner side of the titanium alloy frame 1 is provided with a plurality of grooves, and the grooves are used for pouring aluminum alloy liquid;

[0041] Wherein, the aluminum alloy liquid contains a flow aid.

[0042] Specifically, due to the significant difference in thermal expansion coefficients between titanium alloy and aluminum alloy, this difference will cause significant stress between the two materials when the temperature changes, thereby affecting the adhesion between them. In order to avoid the poor adhesion caused by this stress, the present invention cleverly sets grooves on the inner side of the titanium alloy frame. The original intention of the design of these grooves is to allow aluminum alloy liquid to be poured into them, and after cooling, form a tight mechanical locking structure with the titanium alloy frame, which can significantly improve the adhesion between the two materials.

[0043] As an optional embodiment of the present invention, the groove includes at least one of a dovetail groove 2 or a T-shaped groove 3.

[0044] Specifically, the design of the groove shape can significantly affect the thermal expansion and stress distribution between the titanium alloy frame and the aluminum alloy liquid. For example, a carbon fiber metal composite electronic product body structure provided in patent CN105525336B includes an aluminum alloy frame and a carbon fiber middle frame plate located inside the aluminum alloy frame and integrally composited with the aluminum alloy frame, wherein the aluminum alloy frame has a microporous structure formed by surface corrosion treatment, and the carbon fiber middle frame plate is combined with the surface of the aluminum alloy frame having the microporous structure and is formed into one piece by hot pressing and curing.

[0045] However, the micropores formed by chemical corrosion treatment in this patent cannot be effectively controlled, and may form micropores of various shapes and sizes. When faced with stress caused by differences in thermal expansion coefficients, these micropores cannot effectively manage and control stress, causing the frame structure to deform, crack or produce gaps, thereby affecting the overall airtightness and structural integrity.

[0046] The present application sets a dovetail groove or T-slot structure in the titanium alloy frame, or cleverly combines the two to form a hybrid structure, which exhibits excellent mechanical properties when facing the stress challenge caused by the difference in shrinkage rate between aluminum and titanium. Figure 1 As shown in the figure, these groove structures can effectively resist shrinkage forces in the Y direction and ensure the stability of the structure in this direction; in the X direction, the dovetail groove and T-slot structure, with its unique mortise and tenon design, achieve a firm connection in the X direction, effectively preventing the shrinkage and displacement of the aluminum alloy. In addition, the T-slot structure, with its stable support, provides additional resistance in the Y direction, further enhancing the overall stability of the structure. When the two are used in combination, they can play a synergistic role, allowing the structure to maintain its integrity and airtightness under bidirectional tension. This innovative structural design not only solves the problem caused by the difference in shrinkage rate when aluminum and titanium are combined, but also improves the airtightness and stability of the structure, providing strong support for technological progress and application expansion in related fields.

[0047] As an optional implementation manner of the present invention, the edge of the groove is a smooth curve.

[0048] Specifically, when the aluminum alloy liquid is poured into the groove, especially at the sharp corners of the dovetail groove with complex structure or the T-slot with extremely high stability requirements, stress concentration phenomenon is often inevitable. This stress concentration will pose a severe challenge to the tight combination between the subsequent titanium alloy frame and the aluminum alloy structure. Specifically, it may cause a significant decrease in the airtightness between the two, causing a tiny gap to appear in the interface that should have been tightly fitted, thereby affecting the sealing performance and protection level of the overall structure. At the same time, stress concentration may also weaken the stability of the connection part, increase the deformation risk of the structure under long-term stress conditions, and may even cause connection failure, seriously affecting the service life and safety performance of the product. Therefore, in order to avoid the adverse effects of this stress concentration on the airtightness and stability between the titanium alloy frame and the aluminum alloy structure, the present invention optimizes the design of the groove shape, and makes the edge of the groove a smooth curve by increasing the transition fillet to effectively disperse and relieve stress concentration, thereby ensuring the reliability and durability of the final product.

[0049] As an optional embodiment of the present invention, the groove is connected to the notch (such as Figure 1The dovetail slot notch 21 and T-slot notch 31 shown are 100-500 μm in size;

[0050] The bottom of the groove in the titanium alloy frame (such as Figure 1 The size ratio of the dovetail groove bottom 22 and the T-slot bottom 32 to the groove opening is (2.5-3.5):1.

[0051] Specifically, the present application limits the size ratio of the groove bottom to the groove mouth to (2.5-3.5):1 because, when the aluminum alloy liquid is poured into the groove, the groove designed within this ratio range can better disperse the stress generated by the thermal expansion coefficient of aluminum and titanium.

[0052] As an optional embodiment of the present invention, the flow aid includes one or more of silane, silicone, vapor deposited silicon, aluminum chloride, sodium silicate or magnesium oxide, preferably aluminum chloride.

[0053] Specifically, when facing the groove structure specially designed in the present invention and of relatively small size, due to the inherent surface tension of the aluminum alloy liquid itself, when it is injected into these fine grooves, it will encounter considerable resistance, making the pouring process extremely difficult. This resistance not only makes it difficult for the aluminum alloy liquid to evenly and fully penetrate every corner of the groove, but also greatly increases the risk of failing to completely fill the entire groove structure, thereby affecting the quality and performance of the final product. Therefore, the present application adds a small amount of flow aid to the aluminum alloy liquid to improve the fluidity of the aluminum alloy liquid, making it smoother and easier to flow. Through this improvement, the aluminum alloy liquid can better conform to the complex morphology of the groove structure during the pouring process, and even in the most subtle and difficult-to-reach areas, more uniform filling can be achieved. Moreover, the addition of the flow aid also effectively reduces the surface tension of the aluminum alloy liquid during pouring, which further weakens the physical barrier that originally prevents the aluminum alloy liquid from completely filling the groove. .

[0054] As an optional embodiment of the present invention, the added amount of the flow aid is 0.001-0.01% (such as 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, etc.) of the total mass of the aluminum alloy liquid.

[0055] Specifically, as an effective additive, flow aid can significantly reduce the surface tension of aluminum alloy liquid, thereby greatly improving its flow properties and allowing the aluminum alloy liquid to flow more smoothly during the infusion process. However, although flow aid brings many benefits, the control of its addition amount is a key link that requires careful control.

[0056] Specifically, the amount of flow aid added must be strictly controlled within a reasonable range. This is because an appropriate amount of flow aid can effectively promote the fluidity of aluminum alloy liquid, reduce the formation of bubbles, improve filling efficiency, and ultimately improve the surface quality and overall performance of aluminum alloy internal components. However, if excessive amounts are added, it may have an adverse effect on the crystal growth of aluminum alloy internal components, causing changes in the crystal structure, and further affecting key properties such as the mechanical properties of aluminum alloy internal components. In addition, excessive flow aids may also cause other process problems, such as increasing the viscosity of aluminum alloy liquid, affecting its cooling rate, and may even cause defects inside the casting.

[0057] On the contrary, if the amount of flow aid added is too small, its effect on improving the fluidity of the aluminum alloy liquid will become less obvious and it will not be able to fully play its due role. It will also lead to unstable quality of the internal components of the aluminum alloy and difficulty in meeting the design requirements.

[0058] As an optional embodiment of the present invention, the temperature of the aluminum alloy liquid is 740-780°C (such as 745°C, 750°C, 755°C, 760°C, 765°C, 770°C, 775°C, etc.).

[0059] Specifically, the conventional casting temperature of aluminum alloy is usually set in the range of 630°C to 700°C, which can ensure that the alloy liquid has good fluidity and appropriate solidification characteristics, thereby meeting the needs of most casting processes. However, when faced with the relatively small groove structure specially designed in the present invention, the conventional casting temperature seems to be somewhat powerless. In order to ensure that these fine grooves can be fully and evenly filled with aluminum alloy liquid and achieve the ideal molding effect, we need to make adjustments based on the conventional casting temperature, specifically, to increase the casting temperature by 10°C to 50°C. The temperature of aluminum alloy liquid is closely related to its fluidity: the higher the temperature, the more intense the molecular activity inside the alloy, thus giving it better fluidity. Good fluidity means that the aluminum alloy liquid can flow into and fill every corner of the mold more smoothly, including those small and complex groove parts. In this way, it can not only significantly improve the molding quality of the casting, reduce defects caused by poor filling, such as pores, shrinkage, etc., but also ensure that the final product has higher dimensional accuracy and surface finish. However, if the casting temperature is too high, the amount of air absorbed by the aluminum liquid will increase, making it easy to produce pinholes, shrinkage holes, and surface bubbles in the thick wall of the casting, and accelerate the corrosion of the mold, causing premature aging and cracking of the mold; if the casting temperature is too low, the fluidity is poor, and it is easy to produce defects such as cold shut, flow lines, and insufficient pouring. If the temperature is too low, the aluminum liquid is prone to composition deviation, resulting in hard spots in the casting, affecting the mechanical properties.

[0060] As an optional embodiment of the present invention, the groove is formed by 3D printing.

[0061] As an optional embodiment of the present invention, a plurality of bosses are further provided on the inner side of the titanium alloy frame;

[0062] The boss includes a dovetail boss or a T-shaped boss.

[0063] Specifically, Figure 1 As shown, a plurality of dovetail bosses or T-shaped bosses are provided on the inner side of the titanium alloy frame. The dovetail boss 4 or T-shaped boss 5 is the same size as the dovetail groove 2 or T-shaped groove 3. The purpose of such arrangement is to balance the thermal expansion and stress distribution between the titanium alloy and the aluminum alloy, and to further strengthen the mechanical locking connection force between the titanium alloy frame and the aluminum alloy internal components and improve the bonding force.

[0064] As an optional embodiment of the present invention, the titanium alloy includes one of Ti-6Al-4V titanium alloy, Ti-8Al-1Mo-1V titanium alloy, TC4 titanium alloy or TA18 titanium alloy.

[0065] As an optional embodiment of the present invention, the aluminum alloy includes one of 6013 aluminum alloy, 7R03 aluminum alloy, 6061 aluminum alloy, 6063 aluminum alloy, 7005 aluminum alloy, 7075 aluminum alloy or 2117 aluminum alloy.

[0066] Specifically, groove or boss structures often have complex geometric shapes, and 3D printing technology manufactures objects by stacking materials layer by layer, so it can easily realize the manufacture of such complex shapes. 3D printing technology is an additive manufacturing process that only uses the required materials to manufacture objects, thereby reducing the generation of scrap and waste of materials. This feature is particularly significant for groove or boss structures because it can accurately control the amount of material according to actual needs. In addition, 3D printing technology also helps to achieve green manufacturing and sustainable development. Through 3D printing technology, multiple parts that require multi-step processing and assembly in traditional manufacturing can be designed into an integrated structure. For groove or boss structures, this means that multiple micropores and connecting parts can be integrated into a whole, thereby improving the overall performance and reliability of the product.

[0067] According to a second aspect of the present invention, there is provided a processing technology for the above-mentioned metal part, comprising the following steps:

[0068] S1: 3D printing is used to prepare the titanium alloy frame and the grooves and bosses inside the titanium alloy frame;

[0069] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid, and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0070] S3: Polishing, anodizing and aging heat treatment are performed on the rough metal parts to obtain finished metal parts.

[0071] As an optional embodiment of the present invention, in step S3, the polishing process includes chemical treatment and / or mechanical treatment.

[0072] Specifically, chemical treatment includes pickling, for example: using 30% hydrochloric acid or concentrated nitric acid to clean the rough metal parts;

[0073] Specifically, the purpose of pickling is to remove organic matter, grease, dust and other impurities on the surface of the rough metal parts, so as to provide a clean surface for subsequent anodizing.

[0074] The mechanical treatment includes surface grinding and cleaning.

[0075] Specifically, the surface grinding includes: using a grinding tool to lightly grind the rough metal product to increase the surface area, which is beneficial to the anodic oxidation of the rough metal product in the electrolyte;

[0076] The cleaning process includes: cleaning the surface with alcohol to remove impurities and residues generated during the grinding process.

[0077] As an optional embodiment of the present invention, in step S3, the anodizing is to place the polished metal part in an electrolytic cell, the electrolyte in the electrolytic cell includes 0.5-2 mol / L sulfuric acid solution, 0.5-1.0 mol / L oleic acid hydroxyethyl imidazoline and 0.5-1.0 mol / L sodium sulfate mixture, with a titanium alloy frame as the anode and graphite as the cathode, direct current electrolysis for 20-40s, and the current density is controlled at 0.10-0.30A / cm 2 The bath temperature is controlled at 30-50°C, preferably 40°C. After completion, rinse with deionized water and dry.

[0078] As an optional embodiment of the present invention, in step S3, the aging heat treatment includes: hot pressing and curing the anodized metal part at a curing temperature of 800-950° C. for 30-60 minutes, and cooling;

[0079] Then heat to 500-600℃, keep for 6-10h, and obtain the finished metal part after cooling.

[0080] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0081] Example 1

[0082] The titanium alloy used in this embodiment is Ti-6Al-4V and the aluminum alloy is 7005.

[0083] S1: Use 3D printing to prepare the titanium alloy frame, set up multiple Figure 1 The dovetail slots, T-slots, dovetail bosses and T-bosses shown;

[0084] Among them, the slot opening of the dovetail slot and the T-slot are both 200 μm, and the bottom of the slot is 500 μm;

[0085] Notch: bottom of groove = 1:2.5;

[0086] The sizes of the dovetail boss and the T-shaped boss are the same as the sizes of the dovetail slot and the T-shaped slot.

[0087] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 750° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0088] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.005% of the total mass of the aluminum alloy liquid.

[0089] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0090] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0091] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 55 minutes, and then cooled;

[0092] Then heat to 550°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0093] Example 2

[0094] The titanium alloy used in this embodiment is TC4 and the aluminum alloy is 6013.

[0095] S1: A titanium alloy frame is prepared by 3D printing, and multiple dovetail grooves and dovetail bosses are set;

[0096] Among them, the dovetail groove has a notch of 300 μm and a bottom of 900 μm;

[0097] Notch: bottom of groove = 1:3;

[0098] The size of the dovetail boss is the same as that of the dovetail groove.

[0099] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 770°C), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0100] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.004% of the total mass of the aluminum alloy liquid;

[0101] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0102] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 1 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 0.8 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 30 s. The current density was controlled at 0.30 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0103] The rough anodized metal parts are hot-pressed and cured at a temperature of 900°C for 50 minutes, and then cooled;

[0104] Then heat to 500°C, maintain for 7 hours, and obtain the finished metal part after cooling.

[0105] Example 3

[0106] The titanium alloy used in this embodiment is Ti-8Al-1Mo-1V, and the aluminum alloy is 6061.

[0107] S1: A titanium alloy frame is prepared by 3D printing, and multiple T-slots and T-shaped bosses are set;

[0108] Among them, the dovetail groove has a notch of 100 μm and a bottom of 350 μm;

[0109] Notch: bottom of groove = 1:3.5;

[0110] The size of the T-shaped boss is the same as that of the T-shaped slot.

[0111] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 780° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0112] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.008% of the total mass of the aluminum alloy liquid;

[0113] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0114] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.10 A / cm 2 , the bath temperature is controlled at 30°C, and after completion, it is rinsed with deionized water and dried;

[0115] The rough anodized metal parts are hot-pressed and cured at a temperature of 950°C for 40 minutes, and then cooled;

[0116] Then heat to 600°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0117] Example 4

[0118] The titanium alloy used in this embodiment is TA18 and the aluminum alloy is 6063.

[0119] S1: Use 3D printing to prepare the titanium alloy frame, set up multiple Figure 1 As shown Figure 1 The dovetail slots, T-slots, dovetail bosses and T-bosses shown;

[0120] Among them, the slot opening of the dovetail slot and the T-slot are both 200 μm, and the bottom of the slot is 600 μm;

[0121] Notch: bottom of groove = 1:3;

[0122] The sizes of the dovetail boss and the T-shaped boss are the same as the sizes of the dovetail slot and the T-shaped slot.

[0123] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 750° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0124] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.005% of the total mass of the aluminum alloy liquid;

[0125] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0126] The polished metal parts were roughly placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 1 mol / L sulfuric acid solution, 0.7 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. DC electrolysis was performed for 30 s with a current density of 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0127] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 35 minutes, and then cooled;

[0128] Then heat to 550°C, maintain for 7 hours, and obtain the finished metal part after cooling.

[0129] Example 5

[0130] The titanium alloy used in this embodiment is Ti-6Al-4V and the aluminum alloy is 7075.

[0131] S1: A titanium alloy frame is prepared by 3D printing, and multiple dovetail grooves and dovetail bosses are set;

[0132] Among them, the dovetail groove has a notch of 500 μm and a bottom of 1250 μm;

[0133] Notch: bottom of groove = 1:2.5;

[0134] The size of the dovetail boss is the same as that of the dovetail groove.

[0135] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 740°C), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0136] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.001% of the total mass of the aluminum alloy liquid;

[0137] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0138] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 1 mol / L sulfuric acid solution, 1 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 30 seconds. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0139] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 35 minutes, and then cooled;

[0140] Then heat to 600°C, maintain for 8 hours, and obtain the finished metal part after cooling.

[0141] Comparative Example 1

[0142] The difference between this comparative example and Example 1 is that no grooves and bosses are provided in the titanium alloy frame, specifically:

[0143] The titanium alloy used in this comparative example is Ti-6Al-4V, and the aluminum alloy is 7005.

[0144] S1: Titanium alloy frame prepared by 3D printing;

[0145] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 750° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part.

[0146] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0147] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0148] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 55 minutes, and then cooled;

[0149] Then heat to 550°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0150] Comparative Example 2

[0151] The difference between this comparative example and Example 1 is that the poured aluminum alloy liquid does not contain a flow aid, specifically:

[0152] The titanium alloy used in this comparative example is Ti-6Al-4V, and the aluminum alloy is 7005.

[0153] S1: Use 3D printing to prepare the titanium alloy frame, set up multiple Figure 1 The dovetail slots, T-slots, dovetail bosses and T-bosses shown;

[0154] Among them, the slot opening of the dovetail slot and the T-slot are both 200 μm, and the bottom of the slot is 500 μm;

[0155] Notch: bottom of groove = 1:2.5;

[0156] The sizes of the dovetail boss and the T-shaped boss are the same as the sizes of the dovetail slot and the T-shaped slot.

[0157] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 750° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0158] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0159] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0160] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 55 minutes, and then cooled;

[0161] Then heat to 550°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0162] Comparative Example 3

[0163] The difference between this comparative example and Example 1 is that the temperature of the poured aluminum alloy liquid is 700° C., specifically:

[0164] The titanium alloy used in this comparative example is Ti-6Al-4V, and the aluminum alloy is 7005.

[0165] S1: Use 3D printing to prepare the titanium alloy frame, set up multiple Figure 1 The dovetail slots, T-slots, dovetail bosses and T-bosses shown;

[0166] Among them, the slot opening of the dovetail slot and the T-slot are both 200 μm, and the bottom of the slot is 500 μm;

[0167] Notch: bottom of groove = 1:2.5;

[0168] The sizes of the dovetail boss and the T-shaped boss are the same as the sizes of the dovetail slot and the T-shaped slot.

[0169] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 700° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0170] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.005% of the total mass of the aluminum alloy liquid;

[0171] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0172] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0173] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 55 minutes, and then cooled;

[0174] Then heat to 550°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0175] Comparative Example 4

[0176] The difference between this comparative example and Example 1 is that the addition amount of the flow aid is 0.015%, specifically:

[0177] The titanium alloy used in this comparative example is Ti-6Al-4V, and the aluminum alloy is 7005.

[0178] S1: Use 3D printing to prepare the titanium alloy frame, set up multiple Figure 1 The dovetail slots, T-slots, dovetail bosses and T-bosses shown;

[0179] Among them, the slot opening of the dovetail slot and the T-slot are both 200 μm, and the bottom of the slot is 500 μm;

[0180] Notch: bottom of groove = 1:2.5;

[0181] The sizes of the dovetail boss and the T-shaped boss are the same as the sizes of the dovetail slot and the T-shaped slot.

[0182] S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid (temperature is 750° C.), and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part;

[0183] The flow aid in the aluminum alloy liquid is aluminum chloride, and its addition amount accounts for 0.015% of the total mass of the aluminum alloy liquid;

[0184] S3: The rough metal parts are first pickled (with 30% hydrochloric acid) to remove oxides and contaminants on the metal surface, and then polished in a grinder to obtain a smoother and brighter surface;

[0185] The polished metal parts were placed in an electrolytic cell. The electrolyte in the electrolytic cell included a mixture of 2 mol / L sulfuric acid solution, 1.0 mol / L oleic acid hydroxyethyl imidazoline and 1.0 mol / L sodium sulfate. The titanium alloy frame was used as the anode and graphite was used as the cathode. The DC electrolysis was performed for 40 s. The current density was controlled at 0.20 A / cm 2 , the bath temperature is controlled at 40°C, and after completion, it is rinsed with deionized water and dried;

[0186] The rough anodized metal parts are hot-pressed and cured at a temperature of 850°C for 55 minutes, and then cooled;

[0187] Then heat to 550°C, maintain for 6 hours, and obtain the finished metal part after cooling.

[0188] Performance Test:

[0189] 90 degree peel test: In the peel tester, one end of the sample is fixed and the other end is peeled off at an angle of 90 degrees, and the maximum peel force during the peeling process is measured;

[0190] Impact test: refer to the hammer test in GB / T 2423.55-2006;

[0191] Shear test: refer to ASTM B769.

[0192] Table 1 Components and their corresponding mass percentages in Examples 1-4 and Comparative Examples 1-4

[0193]

[0194] As shown in Table 1, compared with Example 1, since no grooves and bosses are set in the titanium alloy frame in Comparative Example 1, there is a significant difference in the thermal expansion coefficients of the titanium alloy and the aluminum alloy, which causes significant stress to be generated between the two materials when the temperature changes, thereby affecting the adhesion between them, resulting in a significant decrease in the peel strength and shear strength of the metal part, and even cracks after the impact test.

[0195] As shown in Table 1, compared with Example 1, since no flow aid is added to the poured aluminum alloy liquid in Comparative Example 2, the fluidity of the aluminum alloy liquid is poor and the surface tension is also large. Therefore, during the pouring process, due to the small size of the notch, the aluminum alloy liquid cannot be fully poured into some grooves, resulting in a decrease in the adhesion between the aluminum alloy and the titanium alloy frame, affecting the mechanical properties of the metal part.

[0196] As shown in Table 1, compared with Example 1, the temperature of the aluminum alloy liquid poured in Comparative Example 3 is lower, which makes the fluidity of the aluminum alloy liquid worse. Therefore, during the pouring process, due to the small size of the notch, the aluminum alloy liquid cannot be fully poured into some grooves, resulting in a decrease in the adhesion between the aluminum alloy and the titanium alloy frame, affecting the mechanical properties of the metal part.

[0197] As shown in Table 1, compared with Example 1, due to the excessive addition of flow aid in Comparative Example 4, the crystal structure of the aluminum alloy internal component changes, thereby affecting the adhesion between the aluminum alloy internal component and the titanium alloy frame, and further affecting the mechanical properties of the metal parts.

[0198] In summary, the present invention arranges grooves and boss structures on the inner side of the titanium alloy frame, and these grooves allow the aluminum alloy liquid to be poured into them, and form a tight mechanical locking structure with the titanium alloy frame after cooling. This structure can significantly improve the adhesion between the two materials, and adding a flow aid to the aluminum alloy liquid can significantly reduce the surface tension of the aluminum alloy liquid, thereby greatly improving its flow properties, so that the aluminum alloy liquid can flow more smoothly into the designed smaller grooves during the pouring process.

[0199] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A metal part, characterized in that: The metal parts include a titanium alloy frame and an aluminum alloy internal component; A plurality of grooves are provided on the inner side of the titanium alloy frame, and the grooves are used for pouring aluminum alloy liquid; Wherein, the aluminum alloy liquid contains a flow aid.

2. The metal part according to claim 1, characterized in that: The groove comprises at least one of a dovetail groove or a T-slot; The edge of the groove is a smooth curve.

3. The metal member according to claim 2, characterized in that: The size of the notch connecting the groove and the inner side of the titanium alloy frame is 100-500 μm; The size ratio of the groove bottom to the groove mouth is (2.5-3.5):

1.

4. The metal member according to claim 2, characterized in that: The flow aid includes one or more of silane, silicone, vapor deposited silicon, aluminum chloride, sodium silicate or magnesium oxide; The amount of the flow aid added is 0.001-0.01% of the total mass of the aluminum alloy liquid; The temperature of the aluminum alloy liquid is 740-780°C.

5. The metal member according to claim 1, characterized in that: The groove is formed by 3D printing.

6. The metal member according to claim 1, characterized in that: The inner side of the titanium alloy frame is also provided with a plurality of bosses; The boss includes at least one of a dovetail boss and a T-shaped boss.

7. The metal member according to claim 1, characterized in that: The titanium alloy includes one of Ti-6Al-4V titanium alloy, Ti-8Al-1Mo-1V titanium alloy, TC4 titanium alloy or TA18 titanium alloy; And / or, the aluminum alloy includes one of 6013 aluminum alloy, 7R03 aluminum alloy, 6061 aluminum alloy, 6063 aluminum alloy, 7005 aluminum alloy, 7075 aluminum alloy or 2117 aluminum alloy.

8. A process for processing a metal part according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: 3D printing is used to prepare the titanium alloy frame and the grooves and bosses inside the titanium alloy frame; S2: placing a titanium alloy frame in a mold, pouring aluminum alloy liquid, and forming internal components after the aluminum alloy liquid is cooled to obtain a rough metal part; S3: Polishing, anodizing and aging heat treatment are performed on the rough metal parts to obtain finished metal parts.

9. The metal parts processing technology according to claim 7, characterized in that: In step S3, the anodic oxidation is to place the polished metal part in an electrolytic cell, the electrolyte in the electrolytic cell includes a 0.5-2 mol / L sulfuric acid solution, 0.5-1.0 mol / L oleic acid hydroxyethyl imidazoline and 0.5-1.0 mol / L sodium sulfate mixture, a titanium alloy frame as an anode, graphite as a cathode, direct current electrolysis for 20-40 s, and a current density controlled at 0.10-0.30 A / cm 2 , the bath temperature is controlled at 30-50°C, and after completion, it is rinsed with deionized water and dried; And / or, in step S3, the polishing treatment includes chemical treatment and / or mechanical treatment.

10. The metal parts processing technology according to claim 7, characterized in that: In step S3, the aging heat treatment includes: hot pressing and curing the anodized metal part at a curing temperature of 800-950° C. for 30-60 minutes, and cooling; Then heat to 500-600℃, keep for 6-10h, and obtain the finished metal part after cooling.

Citation Information

Patent Citations

  • A carbon fiber metal composite electronic product body structure and its manufacturing method

    CN105525336B

  • Aluminum alloy casting treatment technology

    CN105177325A

  • Aluminum alloy plastic composite mobile phone frame and manufacturing method thereof

    CN106487970A

  • Manufacturing method of titanium-aluminum bimetal composite plate and titanium-aluminum bimetal composite plate

    CN118527636A

  • Method of manufacturing a lightweight bearing

    US20020174545A1